Analysis of Supply and Adequacy of Food Based on Food Balance Sheets (Case Study in Purworejo Regency) - Arif Soesilo (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
One of the factors that cause poverty is the inadequacy of calories from food. The purpose of this study was to find out how much the availability of food ingredients in Purworejo Regency was to meet the needs of the community and to provide an overview of the existing food availability situation. This study used a survey involving 180 respondents from wholesalers in 16 sub-districts in Purworejo Regency, as well as secondary data from related offices/agencies. The method used is a calculation using the Foodstuff Balance which consists of 11 food groups, the level of public consumption of these food groups, to the availability of carbohydrate, protein and fat energy per capita. The results of the analysis obtained: (1) The availability of carbohydrates in Purworejo Regency is 2,619 kcal/cap/day, (2) The availability of Protein is 71.60 grams/cap/day and (3) The availability of Fat is 43.54 grams/day cap/day. Overall the availability of calories and protein in Purworejo has met national standards according to WNPG XI 2018, which is set at 2400 kcal/cap/day, so that the sufficiency of food availability in Purworejo Regency is more than sufficient to meet the needs of its people.